GENDER REPRESENTATION IN TEACHER-STUDENT INTERACTION IN SOCIOLOGY LEARNING: A DISCOURSE ANALYSIS - Atikah Ulayya (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to examine gender representation in teacher-student interaction during Sociology learning at the secondary school level through the Critical Discourse Analysis (AWK) approach of Sara Mills. In the context of education, verbal and nonverbal interactions between teachers and students play an important role in shaping social identity, including gender identity. The results of the study show that in learning practice, there is still a tendency for teachers to reproduce gender stereotypes implicitly and explicitly, such as men's association with leadership and rationality, and women with affection, appearance, and domestic duties. Data collection was carried out by analyzing Sociology learning videos uploaded on TikTok social media. It was found that the language used by teachers was not neutral, but rather loaded with patriarchal ideologies that reinforced traditional gender roles. This hinders the function of education as a means of social liberation. Therefore, critical reflection and teacher training with a gender perspective are needed so that Sociology learning can become a fair and transformative space. This research contributes theoretical and practical insights in building gender-equal class interactions, while strengthening the role of education in creating a more just and inclusive society.